Factores asociados a la diarrea persistente en niños hospitalizados. Un estudio de casos y controles (1996)
ABSTRACT: Introduction. The purpose of this study was to establish the factors associated with the presence of persistent diarrhea in children hospitalized due to diarrheic illnesses at the '"Hospital Universitario San Vicente de Paul" in Medellin, Colombia. Material and methods. In this study, the records of 1, 692 children discharged from the hospital from April 1988 to June 1995 after being diagnosed as having a diarrheic illness were analyzed. Of this total number of patients, 642 (38%) showed persistent diarrhea. Results. A statistically significant association was found between persistent diarrhea and the following: age under 1 year old, with an odds ratio (OR) of 1.79 (95% confidence interval (95 CI) of 1.45.2.21); dysentery, with an OR of 1.88 (95% CI of1.44-2.45); having been previously treated for the same illness, with an OR of I.66 (95% Clof1.35-2.05); having been hospitalized due to diarrhea during the past month, with an OR of 3.13 (95% CI of2.35-4.16); mild malnutrition, with an OR of 1.41 (95% CI of 1.14-1.75); and, advanced malnutrition, with an OR of2.21 (95% CI of 1.72-2.85). The study also revealed a negative association between persistent diarrhea and the following: age over 2 years old, with an OR of 0.39 (95% CI of0.27-0.57); and, normal nutritional condition, with an OR of 0.44 (95% CI of 0.35-0.54). Another association found was between persistent diarrhea and the presence of Salmonella enteritidis in the coproculture, with an OR of2.02 (95% CIof1.50-1.72). The risk of presenting the clinical symptoms suggesting enterocolitis was higher among children with persistent diarrhea, with an OR of 3.76(C195% of 1.54-9.46), as were the risk of sepsis, with an OR of 5.02 (95% CI of 1.87-14.20) and of dying during hospitalization, with an OR of 3.77 (95% CI of 1.54-9.49). Conclusions. Persistent diarrhea is associated with: age under 1 year old, malnutrition and higher mortality among children hospitalized due to diarrheic illnesses.